Caracterização do desenvolvimento larval do pacu, Piaractus mesopotamicus (Holmberg, 1887): morfometria e crescimento isométrico - Paula, Salete de (2012)
This study describes the development and allometric growth patterns of larval Piaractus mesopotamicus from induced reproduction. From hatching until the 19th day, twenty individuals were selected for eight stage of development (yolk sac larval, preflexion, initial of flexion, flexion, end of flexion and post flexion). Later, morphometric measurements were taken of each individual: total length, head length, trunk length, tail (post anal) length, head height, body height, muscle height at anus leveleye diameter, mouth length, caudal peduncle height and caudal peduncle length. Allometric growth coefficients were calculated by linear regression; the changes in the coefficients of growth relate to ontogenetic changes in the priorities of the larvae. During the developmental stages of larval yolk and pre-flexion (mean CT = 3.363 and 5.89 mm), the larvae showed an evident priority for feeding and swimming capabilities. From the flexion stage (mean CT = 9.33 mm) was observed a change in growth priorities, especially those relating to body height, important characteristic for this species. From the post-flexing stage (mean CT = 16.25 mm) a greater propensity to isometry was evident for all coefficients growths. These results confirm the informations that there are different growth patterns for priority functions during ontogeny initial larvae. This study of morphometric and allometric growth of larvae Piaractus mesopotamicus, may assist the fisheries biology, supporting management strategies and conservation of natural populations